Aeronaves Remotamente Pilotadas na fronteira e sua contribuição para a defesa nacional - Gomes, Carlos Filipe Cosentino (2025)
Technological advances have played an important role in the modernization of defense strategies. In this context, the use of Remotely Piloted Aircrafts (RPA ) offers significant benefits, such as continuos monitoring, rapid threat detection and an efficient response capacity. This aims to in-vestigate the use of RPA in the triple border region of Panama (Brazil), considering their strengths and challenges in accordance with national defense documents and their strategic relevance. The investi-gation was conducted through a systematic literature review, using the PRISMA method and analyzing national defense documents. As a result, the article concludes that the use of RPA s in Brazil’s western border zone could occupy an important position in the modernization of defense strategies, con-tributing to border protection and the national security while optimizing resources. Additionally, it identifies certain legal loopholes that hinder the effective integration of RPAs into public policies and defense operations.